EVALUASI TINGKAT KEPATUHAN MINUM OBAT HIPERTENSI PADA PASIEN PROGRAM RUJUK BALIK DI APOTEK MITRA BANJARMASIN - Novia Ariani; Noverda Ayuchecaria (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Hypertension is a major factor causing cardiovascular disease and the highest cause of death in Indonesia. Mortality due to hypertension in Southeast Asia is around 1.5 million/year. In Indonesia based on 2018 Riskesdas amounted to 34.1%, with the highest prevalence in South Kalimantan 44.1%. The level of adherence to taking medication is one of the benchmarks in the success of antihypertensive drug therapy and can be used to determine the most appropriate intervention method used in increasing adherence to taking a patient's medication and knowing the effectiveness of hypertension therapy that is being undertaken by the patient. The purpose of this study was to determine the level of adherence to taking the antihypertensive medication in the patient's Program Rujuk Balik in Mitra Banjarmasin Pharmacy. This type of research is a non-experimental prospective observational with the presentation of data descriptively. The study was conducted at the Mitra Banjarmasin Pharmacy in February to March 2019 with sampling using the saturated sample method of 163 populations. Data collection is done by completing the Medication Adherence Report Scale (MARS) compliance questionnaire sheets. Data processing is processed in the form of an excel recapitulation. Data analysis uses simple frequency distribution tables which are grouped into high, medium and low levels of compliance. The results showed that of the 163 respondents used in this study who had a high level of adherence were 45 respondents (27.61%) and the moderate level of adherence was 118 respondents (72.39%). The conclusions in this study indicate that the level of adherence to taking antihypertensive drugs in patient's Program Rujuk Balik in Mitra Banjarmasin Pharmacy is moderate